Impact of bariatric surgery on premenopausal women's womanliness: A qualitative systematic review and meta-synthesis. - Rebecca Paul; Ellen Andersson; Torsten Olbers; Jessica Frisk; Carina Berterö (PLoS ONE, 2024)
Introduction Obesity is associated with several co-morbidities in women, including disturbed sex hormone regulation with menstrual disturbances, subfertility, hirsutism, and central fat dispersion, all with an impact on sexual function and quality of life. There are few investigations regarding women's experiences of obesity-related altered sex hormone regulation and resolution after bariatric surgery. Objectives This systematic review and interpretive meta-synthesis aim to identify the current qualitative knowledge base concerning women undergoing bariatric surgery and experiences of changes after weight loss, emphasising aspects of womanliness. Methods A systematic review and qualitative meta-synthesis was conducted to gain a deeper and broader understanding of the available knowledge about premenopausal women's experienced changes after bariatric surgery. Relevant papers were identified by systematically searching PubMed, CINAHL, Embase, PsycInfo, PsycArticles, Scopus, Cochrane Library, Web of Science and Open Grey. The quality of the included studies was assessed, and the data was interpreted and synthesised using Gadamer's hermeneutics. The review protocol was registered on PROSPERO (CRD42023394225). Results A total of 10 studies were considered relevant and included in the qualitative meta-synthesis. Three fusions were identified and interpreted as: "Womanliness," "A healthy and functioning body," and "Mind and Body Connection." Women experienced a return to womanliness after undergoing bariatric surgery with restored menstruation cycles, improved fertility and changed hair and fat dispersion signalling restored sex hormones. Women value a return to a healthy and functioning body that improves their experience of life and ability to take part in it. However, women experienced difficulties in adapting mentally to the drastic physical changes that occur after undergoing surgery. Conclusions Women that have undergone bariatric surgery report several benefits to their health and well-being, although difficulties in adapting mentally to changes in outer appearance need to be managed in order to successfully move forward with a new life after surgery.